Animal nutrition with transgenic plants (CABI biotechnology series, 2013)
This book contains 15 chapters that discuss the use of transgenic plants as animal feeds. Topics include the limitations of transgenic plants for animal nutrition; fundamentals of plant biotechnology; nutritional, safety and compositional assessment of feeds from transgenic plants; feeding studies using transgenic plants; the fate of transgenic DNA and expressed proteins; the effect of feeds from transgenic plants on the composition and quality of animal products; feed additives from transgenic microorganisms; socioeconomics and public acceptance of transgenic plants.